Analisis Tren Pembiayaan Dan Simpanan Bank Maslahat Dana Syariah Nusantara Kota Bengkulu Periode 2020-2024. - donnamaycica maycica; Supardi Mursalin; Padlim Hanif (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2026)
Abstract: The development of financing and deposits in Islamic banking is an important indicator in assessing the intermediation function and the level of public trust in Islamic financial institutions. However, research on financing and deposit trends at Islamic Rural Banks (BPRS) in the regions is still relatively limited, particularly at Bank Maslahat Dana Syariah Nusantara in Bengkulu City. This study aims to analyze the financing and deposit trends at Bank Maslahat Dana Syariah Nusantara in Bengkulu City for the period 2020-2024 and the factors influencing them. The study used a descriptive method with a qualitative approach. Data were obtained through interviews, observations, and documentation with informants consisting of internal bank officials and customers. Data analysis was conducted by describing the development of financing and deposits each year, then interpreting the direction of the trends and the factors influencing these changes. The results show that financing experienced an increasing trend from 9,877 million rupiah in 2020 to 20,294 million rupiah in 2024, with financing dominating the MSME productive sector. Deposits also increased from 10,432 million rupiah to 18,837 million rupiah during the same period. This increase indicates that the bank's intermediation function is functioning quite well and that public trust in Islamic banks is growing. Factors influencing this trend include service quality, product suitability, implementation of Islamic principles, contract transparency, community economic conditions, and customer trust. This research is expected to serve as a reference for developing Islamic banking intermediation strategies in the regions.kata kunci: islamic banks, intermediation function, financing trends, deposit trends